Thermodynamic processes. - Belaadi, Salah (ISTE, Ltd. ; Wiley, 2020)
Thermodynamic Processes 2 is devoted to the study of equilibrium between phases in the case of the four changes of physical state: fusion, boiling or vaporization, sublimation and allotropy or transition. It also includes a section that addresses energy's relationship to the zero sum aspect of exergy and thermal cycles. This second volume presents scientific and technical examples - both theoretical and industrial - which are the result of a careful selection, accrued over more than three decades of teaching thermodynamics and in collaboration with the industry sector. The didactic exercises and the practical problems are entirely dedicated to the understanding of this science, and the potential applications for the industrial world. This book is a tool for work and reflection essential for the student in training, as well as the engineer or experienced researcher.